Unveiling the Influence of Financial Attitude, Financial Literacy, and Lifestyle on Decision-Making and Financial Well-Being:AComprehensive Study on Generation Z - Al-Ichwani, Azzahra; Rahayu, Rita (Jurnal Dinamika Manajemen, 2025)
This study examines the influence of financial attitudes, financial literacy, and lifestyle on financial decision-making and financial well-being, with a focus on Generation Z. Utilizing a quantitative approach, data were collected from 306 respondents in West Sumatra through online surveys. The data were analysed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method, employing the Disjointed Two-Stage approach to ensure robustness and accuracy in testing the structural model. The results reveal that financial attitudes and financial literacy significantly enhance financial decision-making, which in turn positively influences financial well-being. Conversely, lifestyle exerts a negative influence on financial decision-making, thereby reducing financial well-being. Financial decision-making mediates the relationship between financial attitude, financial literacy and lifestyle toward financial well-being. This study contributes to the literature by integrating psychological, behavioural, and lifestyle dimensions into a unified model of financial well-being. It provides empirical evidence on the dominant role of financial attitude and the mediating mechanism of financial decision-making among digital-native populations. The findings suggest that targeted financial literacy interventions, value-oriented financial education, and lifestyle awareness programs are essential to foster sound financial decisions and improve financial well-being, especially for Generation Z.